Telfairia occidentalis Ameliorates Streptozotocin-induced Testicular Oxidative stress by Restoring Endogenous Antioxidant Enzyme Activity and Inhibiting Apoptosis, and Pro-inflammatory cytokines - Ujong, Ujong Peter; Odey, Edward Emuru (African Multidisciplinary Journal of Sciences and Artificial Intelligence, 2024)
The study investigated the protective role of Telfairia occidentalis (TO) against Streptozotocin-induced testicular damage in male Wistar rats, by observing the levels of prooxidants, endogenous antioxidant enzymes inflammatory biomarkers, as well as apoptotic proteins. Thirty-five animals were used for this study and shared into five groups of seven animals each. Group 1 (normal control) received distilled water throughout the experiment. Groups 2-5 received 10% fructose ad libitum for 14 days followed by a single injection of 40 mg/kg body weight streptozotocin, intraperitoneally. After confirmation of diabetes mellitus, group 2 rats received 0.5ml distilled water, group 3 received TO (200 mg/kg body weight), group 4 received TO (300 mg/kg body weight) and group 5 received Metformin (300 mg/kg body weight). All treatments lasted for 28 days, followed by the sacrifice of all experimental animals and the harvest of their testes for biochemical analyses. Results revealed that streptozotocin administration decreased the activities of the antioxidant enzymes SOD, GSH, GST, GPx, CAT while elevating MDA levels in groups 2-5 animals when compared with group 1. Treatment with TO showed increased activities of antioxidant enzymes and reduced MDA levels. Furthermore, streptozotocin administration increased the levels of the inflammatory biomarkers MPO, IL-1β, TNF-α, iNOS, COX-2, and the apoptotic protein, caspase-3 in groups 2-5 animals when compared with group 1. However, these elevations were reversed by the administration of TO. In conclusion, Telfairia occidentalis demonstrates significant protective effects on the antioxidant status and inhibits oxidative stress markers, and inflammatory cytokines in the testes of diabetic rats. This indicates its potential therapeutic value in mitigating diabetes-related testicular complications through the modulation of oxidative stress and inflammatory pathways.